Comparison of Indocyanine Green Angiography and Swept-Source Wide-Field Optical Coherence Tomography Angiography in Posterior Uveitis - Tian, Meng; Zeng, Guodong; Tappeiner, Christoph; Zinkernagel, Martin S.; Wolf, Sebastian; Munk, Marion R. (Frontiers in Medicine, 2022)
Purpose: To compare indocyanine green angiography (ICGA) and swept-source wide-field optical coherence tomography angiography (SS-OCTA) for the assessment of patients with posterior uveitis. Method: SS-OCTA montage images of 5x 12x12mm or 2x 15x9mm, covering approximately 70-90 degree of the retina of consecutive patients with posterior uveitis were acquired. The choriocapillaries and choroidal slabs were compared to findings on ICGA. Results: Sixty-eight eyes of 41 patients were included (mean age 47.2±20.4 years; 58.5% female). In 23 (34%) lesions were visible on OCTA, but not discernable on ICGA. In turn, 22 (32.4%) had visible lesions on ICGA, which were not visible on OCTA. Lesion size strongly correlated among ICGA and OCTA choriocapillaries- (CC) (r=0.99, p≤0.0001) and choroidal slabs (r=0.99, p≤0.0001), respectively. The mean lesion size on the late frames of ICGA (8.45±5.47mm2) was larger compared to the lesion size on OCTA CC scan (7.98±5.47mm2, p≤0.0001) and choroidal scan (7.69±5.10mm2, p=0.002), respectively. The lesion size on OCTA CC scan was significantly larger than on the OCTA choroidal scan (p≤0.0001). Conclusion: SS-wide field OCTA may be a promising tool to assess posterior uveitis patients and may replace ICGA to a certain extent in the future.